Differences in transcriptomic and metabolomic analyses of metabolites of shoots on tea plants of different ages and relevant regulatory network - Li, Meng Yuan; Zhang, Yun Zhi; Zhang, Zi You; Zhang, Yan Hui; Ren, Qian Qian; Jin, Shan (Frontiers in Plant Science, 2023)
Two groups of fresh leaves from tea plants at different ages (Group JP：20 years, 200 years, 1200 years tea plants; GroupYX：50 years, 100 years, 400 years tea plants) were chosen as materials, and their differences in gene expression, metabolites and metabolic regulatory network were investigated through transcriptomics and metabonomics. A total of 12706 differentially expressed genes (DEGs) were screened from the fresh tea leaves in the group JP group, of which tea-20 vs tea-200 had the largest number of DEGs, up to 9041 (4459 down-regulated genes, 4582 up-regulated genes). 8971 DEGs were screened from the fresh leaf samples of tea trees in the group YX group, of which the number of DEGs obtained in the tea-50 vs tea-400 comparison combination was the largest, with a total of 3723 (1722 up-regulated genes, 2001 down-regulated genes). Pathway enrichment analysis showed that most up-regulated DEGs and their related metabolic pathways were similar in the two groups, the metabolic pathways of common significant enrichment included flavonoid biosynthesis, phenylpropane biosynthesis, carbon metabolism, amino acid biosynthesis and plant pathogen interaction. Metabonomics results showed that 72 differential metabolites and 117 differential metabolites were screened from JP group and YX group respectively. Most of the different metabolites in the two groups were flavonoids, phenolic acids, amino acids and their derivatives. Among them, the number of down-regulated flavonoids in older tea plants is generally more than the number of up-regulated flavonoids. Moreover, according to sensory evaluation results of dried tea of fresh leaves from tea plants at different ages, Tea-1200 and Tea-400 showed the highest sensory evaluation scores in their groups. With the increase of plant age, the fragrance of tea was more elegant and it changed from dense scent to faint scent, the tea tastes sweet and its freshness increases, while the sense of astringency was weakened and the concentration declined. Therefore, the quality difference of tea with different tree ages is mainly related to secondary metabolic pathways such as flavonoid biosynthesis pathway.